2003
DOI: 10.1093/ajcn/77.4.1048s
|View full text |Cite
|
Sign up to set email alerts
|

Dietary advice in clinical practice: the views of general practitioners in Europe

Abstract: GPs think that obesity is not easy to handle in practice. Most GPs have dietary tools in the office and think that nurses play an important role in advising patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 3 publications
3
19
1
Order By: Relevance
“…However, a noticeable gap exists between the physicians' attitudes and knowledge regarding weight management and their current practices. This is demonstrated by the fact that only one-third of respondents would identify their patients' weight problems on regular basis despite that the majority agreed to advice about weight loss spontaneously, similar to what has been found in an earlier study (33) . Physicians also seemed to identify weight problems as part of chronic disease care more often than for screening purposes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, a noticeable gap exists between the physicians' attitudes and knowledge regarding weight management and their current practices. This is demonstrated by the fact that only one-third of respondents would identify their patients' weight problems on regular basis despite that the majority agreed to advice about weight loss spontaneously, similar to what has been found in an earlier study (33) . Physicians also seemed to identify weight problems as part of chronic disease care more often than for screening purposes.…”
Section: Discussionsupporting
confidence: 80%
“…This may have overestimated the actual practice as it is difficult to assume with certainty that measured weight was used to calculate BMI and was followed by the appropriate action. This should be considered when comparing these findings with results from developed countries, whose physicians reported measuring BMI less frequently (33) .…”
Section: Discussionmentioning
confidence: 90%
“…The results of EUROPREV research, aimed to access GP's knowledge and attitudes in implementing preventive and health promotion activities and to describe tools used by European GPs in advising patients about dietary practice, showed that 56% of GPs believe that the implementation of these activities is difficult and 58% are skeptical about helping patients achieve or maintain normal weight (Brotons et al, 2003). Other surveys have shown similar results (Grant et al, 1998;McAvoy et al, 1999).…”
Section: Discussionmentioning
confidence: 88%
“…The participants expressed their minimal feedback as ''yeah, well, hmm'' (see Tables II and III). The feedback of the patient [11] might be a comment on not being able to exercise, a clarification, or short responses to indirect questions.…”
Section: Opening Themes Of Counselling Sessions and Participants' Feementioning
confidence: 99%